Immunomodulation as Rescue for Chronic Atonic Skin Wounds. Issue 4 (April 2018) - Opdenakker, Ghislain; Van Damme, Jo; Vranckx, Jan Jeroen
Abstract : Chronic skin wounds, caused by arterial or venous insufficiency or by physical pressure, constitute an increasing medical problem as populations age. Whereas typical wounds are characterized by local inflammation that participates in the healing process, atonic wounds lack inflammatory markers, such as neutrophil infiltration, and generally do not heal. Recently, prominent roles in the immunopathology of chronic wounds were attributed to dysregulations in specific cytokines, chemokines, matrix metalloproteinases (MMPs), and their substrates. Together with the complement system, these molecular players provide necessary defense against infections, initiate angiogenesis, and prepare tissue reconstitution. Here, we review the current state of the field and include the concept that, aside from surgery and stem cell therapy, healing may be enhanced by immunomodulating agents. Highlights: Chronic atonic wounds are caused by vascular defects leading to local necrosis and inflammation. Unlike acute wounds, chronic wounds do not spontaneously heal. Insights into the immunobiology of both acute and chronic wounds are offering new perspectives for treatments aimed at 'restarting' the wound-healing process. Importantly, chronic wounds may be 'stuck' at distinct stages of healing. Targeting of proteases or use of recombinant proteases, such as MMPs, can favor clearance of dead cells and tissue and improve wound healing. Modulation of cytokines and chemokines to restore the normal inflammatory process is also being investigated, with promising results.